2009
DOI: 10.1161/strokeaha.109.560714
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning-Induced Cerebral Ischemic Tolerance

Abstract: Background and Purpose-The importance of bioactive lipid signaling under physiological and pathophysiological conditions is progressively becoming recognized. The disparate distribution of sphingosine kinase (SphK) isoform activity in normal and ischemic brain, particularly the large excess of SphK2 in cerebral microvascular endothelial cells, suggests potentially unique cell-and region-specific signaling by its product sphingosine-1-phosphate. The present study sought to test the isoform-specific role of SphK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 38 publications
2
112
0
1
Order By: Relevance
“…Sphingosine-1-phosphate is produced by two sphingosine kinase (SphK) isoforms, SphK1 and SphK2, which often exhibit differing effects. Because only SphK2 protein levels and activity increased in cortical microvessels following HPC, and nonspecific SphK inhibition abrogated HPCs neuroprotective effects (Wacker et al, 2009), an isoformspecific contribution of SphK2 to ischemic tolerance was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingosine-1-phosphate is produced by two sphingosine kinase (SphK) isoforms, SphK1 and SphK2, which often exhibit differing effects. Because only SphK2 protein levels and activity increased in cortical microvessels following HPC, and nonspecific SphK inhibition abrogated HPCs neuroprotective effects (Wacker et al, 2009), an isoformspecific contribution of SphK2 to ischemic tolerance was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have also indicated that hypoxic preconditioning reduced the volume of cerebral infarction and edema (41) and attenuated the loss of myocardial contractility (3) immediately after sublethal ischemic insult. Therefore, we speculate that increased O 2 delivery/utilization and resistance to acute hypoxic/ischemic stresses conferred by hypoxic interventions improves exercise performance and is effective for preventing and treating cerebrovascular/cardiovascular diseases.…”
mentioning
confidence: 99%
“…The PI3K/Akt signaling cascade has been shown to play a key role in preventing apoptosis under hypoxic or ischemic conditions. Hypoxic preconditioning (HPC) has also been investigated in the contest of cerebral ischemia [105,108] . With respect to elucidating the molecular basis of preconditioning-induced tolerance, Yung et al [106] showed that hypoxic preconditioning significantly reduced infarct volume and improved neurological outcome in wild-type and SphK1-/-, but not in SphK2-/-mice.…”
Section: Role Of Sphingolipids In Cerebrovascular Diseasementioning
confidence: 99%